PEMANFAATAN MEDIA PAPAN CERITA RAKYAT DALAM KETERAMPILAN BERBICARA MAHASISWA BIPA LEVEL 6 - Putri Utami Dewi Putri; Khaerunnisa (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
This study intends to describe the benefits of using folklore board media in improving the speaking skills of BIPA students from Thailand. This research method uses a qualitative descriptive method which will produce data in the form of a series of words that will form paragraph by paragraph. The data in this study is the use of folklore board media. Data acquisition is done by direct observation. The source of this research is focused on a series of BIPA learning processes with Thai students. The research subjects were BIPA students who joined the learning program carried out by the author. Data collection is in the form of listening and note-taking techniques. The results showed that the folklore board media provided benefits as a means of introducing Indonesian culture in the sociocultural aspect. The benefits of the folklore board media are as follows: (1) learning is packaged in an attractive and communicative way, (2) students are more active in learning, (3) a means of introducing culture, (4) innovation of new and meaningful teaching materials, (5) making it easier for students in his memory. Keywords: BIPA, Speaking Skills, Media.